Equity research | Netflix Inc. (Nflx) - the financial and business challenges of Netflix - Kallel, Mehdi (2021)
The aim of this report is to conduct an equity valuation on Netflix and provide an overview on its current and future state from an economic and business perspectives. Our analysis has a special focus placed for this year, due to the significant impact of the global pandemic. This paper will examine the multiple threats facing Netflix in the short term and long term. We have consulted a wide varietyofsourcesandstudiedannualandquarterlyreportspublishedbythe company. After considering the implicit risks, we determined a target share price for the end of 2021 at$605.